2013
DOI: 10.1086/671052
|View full text |Cite
|
Sign up to set email alerts
|

Extended Self in a Digital World: Table 1.

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
628
1
94

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,226 publications
(740 citation statements)
references
References 120 publications
17
628
1
94
Order By: Relevance
“…The objects we call our own therefore increasingly exist in digital form (Belk 2013a;Denegri-Knott and Molesworth 2010;Lehdonvirta 2012), yet present significant opportunities for profit for companies. To illustrate, in 2013, the most obvious forms of digital content accounted for 50% of UK music and video revenue, (Mintel 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objects we call our own therefore increasingly exist in digital form (Belk 2013a;Denegri-Knott and Molesworth 2010;Lehdonvirta 2012), yet present significant opportunities for profit for companies. To illustrate, in 2013, the most obvious forms of digital content accounted for 50% of UK music and video revenue, (Mintel 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Having established a context in both market innovation in labour and commodity form, and critiques of production as exploited consumer labour, we offer four contributions. Firstly, we extend the scope of studies on possession in situations of non-ownership and accessbased consumption (Belk 2013a;2013b;Bardhi, Eckhardt & Arnould 2012;Chen 2010) complementing the language of mediation with that of networks. Drawing from Actor-Network Theory (ANT) (Latour 1993; we argue that hosted DCOs can be enacted in multiple networks simultaneously, producing conflicting ontologies whereby DCOs are concurrently enacted as assets by companies, and as possessions by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Fong & Mar (2015) confirmed how individuals customized or chose avatars which reflected and represented themselves in some manner, including the very clothes that were chosen. For many users the actual gender chosen creates a connection with that avatar (Belk, 2013). Whilst gender swapping does occur in VWs (Ducheneaut et al, 2009), and it is easy to pass oneself off as the opposite gender, it could be significant as to whether these novice users chose a gender consistent (or not) with their real life gender.…”
Section: Avatars and Identitymentioning
confidence: 99%
“…Meadows (as cited 2008 in Belk, 2013) suggests that if people make an avatar "of the same gender, age, and race, it feels like you on a psycho-physiological level" (p. 481). If the avatar looks similar to our real life selves, it is more likely that we will have some attachment to that avatar.…”
Section: Avatars and Gendermentioning
confidence: 99%
“…According to Jyrinki and Leipamaa-Leskinen (2006), this construct include consumers' personal and social aspects, symbolic and functional aspects and control and attachment aspects. Belk (2013) explained that areas of consumption that can be impacted by the concept of extended-self include our possession of pets. Belk (1988) cited the works of Secord (1968) who posited that pet owners develop the attitude "love me, love my dog" when pets are part of the owner's self.…”
Section: Self-extension Constructmentioning
confidence: 99%